Radiological Imaging and Analysis of Laboratory Values in Case of Acute Ischemic Stroke - Necmi Baykan; Mustafa Alpaslan (Genel Tıp Dergisi)
Background: The rate of death and disability due to acute ischemic stroke ranks second in the world. In this study it was planned to analyze the demographic characteristics and additional diseases in the etiology as well as radiological imaging and laboratory values in patients with ischemic stroke. Materials and Methods: This study was conducted retrospectively by analyzing the patients hospitalized with the diagnosis of ischemic stroke from the emergency department between 01.01.2022 and 31.12.2022. Routine laboratory values, lipids, vitamin levels, radiological imaging and tests for etiology were analyzed in the patients. Results: One hundred seventy seven patients were analyzed in the study. 53.1% of the patients were male. The mean age was 75±12.75 years. The most common comorbidities were hypertension, diabetes and hyperlipidemia. As ischemic infarction, involvement was most common in the areas fed by the middle cerebral artery. In the carotid and/or vertebral doppler ultrasonography performed in the patients, plaque was observed in the vessels at a rate of 83.1%. According to the transthoracic echocardiographic findings, 79.3% of the patients were found to have heart valve pathology. Pathologically the majority of patients had hyperglycemia, vitamin D deficiency and low HDL cholesterol levels. Thrombolytic therapy was applied in six patients and three patients benefited and one patient died due to bleeding. 13.6% of the patients were treated in the intensive care unit. Conclusion: The risk of ischemic stroke increases in advanced age. Hypertension and diabetes are among the most important risk factors. Vitamin D and vitamin B12 deficiency and folic acid deficiency pose a risk in terms of atherosclerosis. At the same time, low HDL cholesterol levels increase the risk of stroke. These factors which are considered as preventable causes in etiology should be controlled with treatment.